Madagascar Beetle, Leichenum canaliculatum variegatum (King) (Insecta: Coleoptera: Tenebrionidae) - James C. Dunford; Warren E. Steiner, Jr. (EDIS, 2007)
EENY-399, a 7-page illustrated fact sheet by James C. Dunford and Warren E. Steiner, is part of the Featured Creatures Collection. It describes this cosmopolitan beetle which can be found in sandy areas in Florida, its synonymy, distribution, description, habits and importance, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, May 2007.